Effective-notch-stress-based fatigue evaluation of rib-deck welds integrating the full-range S—N curve concept. (April 2021) - Wang, Qiudong; Ji, Bohai; Gao, Tian; Fu, Zhongqiu
Abstract: Compared with the nominal and hot-spot stress, the effective notch stress could present more accurate stress state by involving the notch stress induced by weld bead. Inspired by the concept of full-range SN curve, a new notch stress-based fatigue evaluation framework is proposed in this study. The proposed fatigue evaluation framework reasonably considers the material types, welding residual stress, mean stress effect and notch stress concentration. Fatigue testing data of 60 rib-deck welded specimens are extracted to validate the feasibility of the proposed framework. Field monitoring in a real cable-stayed bridge was also carried out as a case study to present the application of the proposed framework. Results show that the proposed fatigue evaluation framework is feasible and reliable for the evaluation of fatigue testing results of rib-deck welded specimens. Instead of the Goodman method and SWT method, Walker equation is recommended to take into consideration the mean stress effect. In engineering application, the proposed fatigue evaluation framework provides more conservative prediction results compared with code recommended FAT225 SN curve, which is applicable to important components where fatigue cracking is not allowed. Graphical abstract: Unlabelled Image Highlights: A novel fatigue evaluation framework for rib-deck welds is proposed. Multiple factors influencing the fatigue performance are considered in the evaluation framework. Fatigue testing data of 60 specimens is extracted to validate the framework. Field measurement of a cable-stayed bridge is conducted as a case study.